Pengaruh Reputasi Underwriter, Return On Equity, dan Umur Perusahaan Syariah Terhadap Underpricing (Studi Pada Perusahaan Yang Teregistrasi di BEI Tahun 2018-2021) - Chrisnanda, Widya Andhi; Raharja, Surya (ITB AAS INDONESIA Surakarta, 2023)
This research aims to determine the influence of Underwriter reputation, Return On Equity, and Company Age on Underpricing (Study of Companies Registered on the BEI in 2018-2021)The samples used in this research are companies that were newly registered on the IDX in 2018-2021. Things that influence the level of Underpricing are proxied as ROE, Company Age, and Underwriter Reputation. Companies that registered on the stock exchange before and during Covid-19 were involved in moderating the underpricing. Company age has a significant negative effect on underpricing, the longer the company's age reduces underpricing. Return On Equity has no significant effect on underpricing. The higher ROE does not reduce the level of underpricing. Underwriter reputation does not have a significant effect on underpricing. The influence of Covid-19 does not moderate the relationship between company age, ROE and underwriter reputation with underpricing